The Needs Analysis Of English For Accounting In SMK Negeri 2 Sidrap - Andi Asrifan; Syamsu T; Andi Sadapotto; Kamridah .; Nurdiyanti N (La Ogi : English Language Journal, 2023)
This research analyzes the accounting students’ need in learning English at SMK N 2 Sidrap due to the accounting students learn English using English textbook which has same content with other majors. In fact, the school has four distinctive majors. The subject of this research is the eleventh grade of accounting students in XI AKL 1. This research used descriptive qualitative research with observation checklist, teacher interview and questionnaire as the tools in collecting data. To analyze the data, the researcher involved five activities; observing English teaching and learning process, teacher interview, giving questionnaire to the accounting students, analyzing and describing the obtained data, and calculating percentage of students’ answer in questionnaire. The result of this research shows that the eleventh grade of accounting students in XI AKL 1 needs more specific English material and English skill in accounting field. In addition, based on classroom observation, in teaching process the teacher requires to find appropriate way that can make the students more interesting and active. Therefore, to maximize their competence in accounting activities, the accounting students hope that the school can design ESP program.